1986
DOI: 10.1182/blood.v68.6.1207.1207
|View full text |Cite
|
Sign up to set email alerts
|

The heterogeneity of type IIA von Willebrand's disease: studies with protease inhibitors

Abstract: The absence of large von Willebrand factor (vWF) multimers from plasma is a characteristic of Type IIA von Willebrand's disease (vWD) and is thought to contribute to the clinical expression of this disorder. Recently, three IIA patients have been reported in whom intermediate and large multimers could be restored if blood were collected in 5 mm EDTA, 6 mmol/L N-ethylmaleimide, and 1 mmol/L leupeptin. This suggested that absence of large multimers resulted from in vitro proteolysis. We have now collected blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

1987
1987
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(17 citation statements)
references
References 7 publications
1
16
0
Order By: Relevance
“…Interestingly, platelet lysates demonstrated a decrease of large vWF multimers for G1505L and S1506L mutants (group 1 defect) but a normal pattern for the G1505E and R1597W mutants (group 2 defect). Battle et al 46,47 and Michiels et al 22 observed heterogeneity of mild, moderate, and severe type 2A vWD with regard to bleeding symptoms, laboratory phenotypes, and response to DDAVP (Table 6). Mild type 2A vWD is characterized by normal or subnormal values for FVIII:C and vWF:Ag; low vWF:RCo values > 0.20; normal RIPA; a good but transient correction of BT, FVIII:C, and vWF parameters; and large multimers for a few hours after DDAVP ( Fig.…”
Section: Type 2 Vwdmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, platelet lysates demonstrated a decrease of large vWF multimers for G1505L and S1506L mutants (group 1 defect) but a normal pattern for the G1505E and R1597W mutants (group 2 defect). Battle et al 46,47 and Michiels et al 22 observed heterogeneity of mild, moderate, and severe type 2A vWD with regard to bleeding symptoms, laboratory phenotypes, and response to DDAVP (Table 6). Mild type 2A vWD is characterized by normal or subnormal values for FVIII:C and vWF:Ag; low vWF:RCo values > 0.20; normal RIPA; a good but transient correction of BT, FVIII:C, and vWF parameters; and large multimers for a few hours after DDAVP ( Fig.…”
Section: Type 2 Vwdmentioning
confidence: 99%
“…6). 22,46,47 Most patients with type 2A vWD show only a transient minor or a poor response to DDAVP, with no correction of the BT despite some increase of vWF:RCo (Fig. 6), and therefore are candidates for FVIII/vWF concentrate substitution for the treatment and prophylaxis of bleeding symptoms.…”
Section: Ddavp In Type 2 Vwdmentioning
confidence: 99%
See 1 more Smart Citation
“…A minority of type 2A have mild vWD characterized by near normal to slightly prolonged values for BT, normal FVIII:C and vWF:Ag, low vWF:RCo and vWF:CB levels, a normal RIPA, and complete correction of BT and functional vWF parameters to normal for only a few hours, followed by short half-life times for vWF:RCo and vWF:CB. 4,5,12,13 This mild type 2A vWD has a transiently complete response to DDAVP that may be good enough for the treatment and prophylaxis of minor bleedings. [3][4][5]11 Most type 2A vWD patients have pronounced or very low vWF:RCo, prolonged (markedly) BT, PFA-100 CT longer than 250 seconds, and show only a transient minor or a poor response to DDAVP with no correction of the BT despite some increase of vWF:RCo.…”
Section: The Response Of Bt Fviii:c and Vwf Parameters To Ddavp In mentioning
confidence: 98%
“…However, the mutant vWF has an increased sensitivity to proteolytic degradation in plasma, resulting in decreased plasma high-molecularweight multimers but a normal platelet vWF multimer pattern. 68 The cleavage site in a subset of patients with type 2A vWD was shown to be the Tyr842-Met843 bond, in which mutations may result in a conformational change, resulting in increased sensitivity to proteolysis.…”
Section: Type 2a Vwdmentioning
confidence: 99%